EFFECT OF TRIMLINE DESIGN AND ATTACHMENTS ON THE RETENTION FORCE OF CLEAR ALIGNERS: AN IN VITRO STUDY (Vietnam Journal of Community Medicine, 2026)
Objective: Clear aligner therapy has become increasingly popular due to its esthetic advantages and patient convenience. However, the effectiveness of tooth movement largely depends on the fit of the aligner on the dental arch, which is closely related to its retention. This study aimed to evaluate the effects of trimline design and the presence of attachments on the retention force of clear aligners under in vitro conditions.Methods: An in vitro experimental study was conducted using clear aligners fabricated from thermoplastic material (Zendura, Bay Materials, USA) on standardized 3D-printed maxillary models. Three trimline designs were investigated: scalloped gingival margin, straight cut at the gingival zenith, and straight cut above the gingival zenith. Each design was tested under two conditions: with and without attachments, resulting in six experimental groups. Retention force was measured using a universal testing machine (UTM) by vertically dislodging the aligners from the dental model at a constant crosshead speed. Data were analyzed using two-way ANOVA followed by Tukey post hoc tests, with a significance level set at p < 0.05.Results: Retention force differed significantly among trimline designs and with the presence of attachments. The scalloped margin without attachments showed the lowest retention force (3.21 ± 0.97 N), whereas the high trimline with attachments demonstrated the highest retention force (26.57 ± 1.85 N). Within the same trimline design, the use of attachments increased retention, particularly in the scalloped and high trimline groups. Additionally, both with and without attachments, the high trimline consistently exhibited greater retention than the straight and scalloped designs.Conclusion: Both trimline design and the presence of attachments significantly influence the retention of clear aligners. The high trimline provides the greatest retention, while the scalloped design yields the lowest. The use of attachments can enhance aligner retention, especially in designs with inherently lower retention.
Keywords: khay chỉnh nha trong suốt, lực lưu giữ khay, thiết kế viền khay, attachment, clear aligner.